The hyperthyroidism in gestational trophoblastic disease: a case report - Hokman, Selvi; Wulandari, Dewi Catur (International Journal of Advances in Medicine, 2023)
Gestational trophoblastic disease, also referred to as GTD, is an extremely rare form of pregnancy-related complication that can arise. It covers a wide range of conditions, from choriocarcinoma to molar pregnancy. Patients who are diagnosed with gestational trophoblastic disease have an increased likelihood of developing hyperthyroidism. It is speculated that this occurs as a result of molecular mimicry that exists between human chorionic gonadotrophin (hCG) and thyroid-stimulating hormone (TSH), which results in cross-reactivity with the TSH receptor. This would explain why the two molecules would react similarly to each other. The gestational trophoblastic disease-induced thyroid storm is an extremely rare but potentially fatal complication that can arise during pregnancy. It is necessary to detect and treat this complication as soon as possible in order to prevent additional complications from occurring. Once the patient’s hemodynamic status has been stabilized, the removal of the mole is the primary component of the definitive treatment that will be administered. In most cases, hyperthyroidism usually resolves once the gestational trophoblastic disease has been successfully treated and the hCG levels have been brought back to normal.